KEDUDUKAN PENETAPAN PENGADILAN NEGERI TERKAIT PERKAWINAN BEDA AGAMA DALAM PERSPEKTIF SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 - Milenia, Cantika Ayu; Firdaus, Emilda; Zulhidayat, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The diversity of religions and beliefs in Indonesia has led to the occurrence of marriagesbetween followers of different religions and beliefs, commonly referred to as interfaithmarriages. Interfaith marriages should not occur based on Article 2 paragraph (1) inconjunction with Article 8 sub f of the Marriage Law and the Supreme Court Circular LetterNumber 2 of 2023. This study discusses the Position of the District Court Decision Number423/Pdt.P/2023/PN Jkt.Utr in adjudicating interfaith marriage applications from theperspective of the Supreme Court Circular Letter Number 2 of 2023 and the Synchronizationof the District Court Decision Number 423/Pdt.P/2023/PN Jkt.Utr with the Supreme CourtCircular Letter Number 2 of 2023.This research employs a normative legal research method by examining the core issuesthrough a legislative and regulatory research approach related to legal issues. The data sourcesconsist of secondary data, which includes primary legal materials, secondary legal materials,and tertiary legal materials. The data collection method was conducted through literature study,followed by normative qualitative data analysis methods.Based on the research results and discussion, the Position of the District Court DecisionNumber 423/Pdt.P/2023/PN Jkt.Utr contradicts the Guidelines in the Supreme Court CircularLetter Number 2 of 2023. The District Court Decision Number 423/Pdt.P/2023/PN Jkt.Utr andthe Supreme Court Circular Letter Number 2 of 2023, based on the theory of the legislativehierarchy, do not synchronize. The Supreme Court Circular Letter No. 2 of 2023 contains policyregulations and guidelines for judges in adjudicating interfaith marriage applications. However,the District Court Decision Number 423/Pdt.P/2023/PN Jkt.Utr, in approving the interfaithmarriage case, only refers to Article 35 Letter a of Law Number 23 of 2006 concerningPopulation Administration. Judges should be more cautious in deciding on interfaith marriageapplications and also refer to the Marriage Law, Supreme Court Circular Letter Number 2 of2023, and other related regulations regarding the regulation of interfaith marriages so that legalcertainty in a court decision is properly implemented.Keywords: Court Decision, Interfaith, Circular Letter